EFFECTS OF DIFFERENT DOSES OF THE FORMICIDE “CITROMAX” ON THE CONTROL OF Acromyrmex lundi (HYMENOPTERA: FORMICIDAE) - Edison Bisognin Cantarelli; Ervandil Corrêa Costa; Leonardo da Silva Oliveira; Edison Rogério Perrando (Ciência Florestal, 2010)
The objective of this study was the analysis of the effect of the formicide “Citromax”, formulated with Ateleia glazioviana, in different doses on the control of Acromyrmex lundi, in native field in São Sepé county,  Rio Grande do Sul, Brazil. Four treatments were analyzed, constituted of doses of 5, 10 and 15g of “Citromax” and 10g of “Mirex-S” (sulphluramide 0,3%) in each nest. The statistical design was completely randomized with 10 repetitions, considering each nest as one repetition. The effectiveness was evaluated in the 1st, 5th, 10th, 15th and 20th day after treatment application. The obtained results allow to conclude that “Citromax” shows an impact action, because there was a high percentage of control in the first five days. The Acromyrmex lundi control due to “Citromax” formicide was efficient in all the evaluated doses, obtaining a control percentage up to 85%. The influence of net size was not observed in relation to the percentage control.